DIFUSI INOVASI GAMELAN VIRTUAL UNTUK PEMBELAJARAN - Urip Wahyono (SENDIKRAF Jurnal Pendidikan Seni dan Industri Kreatif, 2023)
LLearning gamelan is starting to gain a lot of interest. It can be seen from the increasing demandfor learning gamelan in primary and secondary as well as vocational schools in the DaerahIstimewa Yogyakarta Province in particular. However, one of the existing obstacles is the limitedprocurement of gamelan set due to the high price of gamelan instruments, which cost up tohundreds of millions. Therefore, it needs to be a breakthrough way to solve this problem so thatstudents can learn gamelan without using conventional gamelan equipment. One of which isutilizing technological developments as an alternative learning to support gamelan learning. Theuse of media in the learning process is an effort to improve the quality of the learning processwhich can ultimately improve the quality of student learning outcomes. Accordingly, a diffusionof innovation is very necessary in order to stay relevant and not to be left behind from the currentdevelopments. We must always innovate so that we can continue to follow the direction of thedevelopments and meet the needs of many users from millennials and generation Z. This diffusionof innovation requires breakthroughs in the field of arts and culture education, namely bycreating applications that collaborate technology and arts so that it remains popular and ofinterest to students. It is expected that virtual gamelan will be a new breakthrough to answer thechallenges of developing educational technology that is used by educators and students as analternative learning medium nowadays. Belajar gamelan mulai banyak diminati, hal ini terlihat adanya permintaan untuk belajargamelan yang semakin meningkat di satuan pendidikan baik dari Jenjang dasar dan menengahmaupun SMK di Wilayah D.I Yogyakarta khususnya. Namun yang masih menjadi kendala yaituketerbatasan pengadaan gamelan, dikarenakan mahalnya harga instrumen gamelan yangmencapai ratusan juta. Oleh karena itu perlu ada terobosan untuk memecahkan masalah tersebutagar siswa dapat belajar gamelan tanpa menggunakan peralatan gamelan yang konvensional,salah satunya memanfaatkan perkembangan teknologi sebagai alternatif belajar untukmendukung dalam belajar gamelan. Penggunaan media dalam proses pembelajaran merupakansalah satu upaya meningkatkan kualitas proses pembelajaran yang pada akhirnya dapatmeningkatkan kualitas hasil belajar siswa. Melihat hal tersebut sebuah difusi inovasi sangatdiperlukan agar tidak tertinggal jauh dengan perkembangan jaman dan begitu juga bidangpendidikan, kita harus selalu berinovasi agar tetap bisa mengikuti arah perkembangan jaman danmemenuhi kebutuhan pengguna yang banyak dari kalangan milenial dan generasi Z. Difusiinovasi ini diperlukan terobosan di bidang pendidikan seni dan budaya, yaitu dengan caramembuat aplikasi yang mengkolaborasikan teknologi dan seni agar tetap digemari dan diminatioleh kalangan pelajar. Gamelan virtual diharapkan menjadi sebuah terobosan baru untukmenjawab tantangan perkembangan teknologi pendidikan yang digunakan para pendidik maupunpeserta didik sebagai media pembelajaran alternatif pembelajaran saat ini.